Asymetria informacji w modelu pryncypał-agent – wyniki badań eksperymentalnych - Bernat, Tomasz; Hawran, Katarzyna; Kowalik, Joanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The purpose of this article is to analyze the classical assumption that in the absence of sufficient information in the market transaction there is a problem of asymmetry. In addition it verified the assumption that you understand the transaction allows the Company to take further decisions – less risky. In the presented article first defines the concepts of asymmetric information and a description of the model pryncypał-agent. Then pointed out the methodology of the experiment and describes the test result. The final part of the article presents the conclusions. The study was based on economic experiment carried out on a random sample of students of third degree at the Faculty of Economics and Management in Szczecin. Results of this study demonstrated the occurrence of the phenomenon of information asymmetry. It confirmed the situation in which one party had more information than the other to a diverse range, which resulted in a favorable decision making.
Keywords: information asymmetry; economy; risk